THE MATRYOSHKA OF HEALTHCARE FACILITIES: A LEGAL ANALYSIS ON ESTABLISHING LAYERED PRIVATE HEALTHCARE FACILITIES IN MALAYSIA - Hanapi, Nur Liyana (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
This manuscript evaluates whether Malaysia should permit layered private healthcare facilities—licensed hosts that co‑locate third‑party providers—and specifies the legal and governance pre‑conditions for safe adoption. Drawing on Act 586 and the 2006 Regulations, recent Malaysian jurisprudence on non‑delegable duties, and comparative oversight models from the United States (CMS[1]), Singapore (HCSA[2]), and England (CQC[3]), the analysis reaches a consistent conclusion: shared premises do not dilute accountability. The paper reframes the problem through a single research question—under what auditable safeguards, if any, should Malaysia license layered facilities—and advances four guardrail domains: (i) independent compliance proven by each co‑located entity; (ii) transparent patient attribution and ethical advertising; (iii) conflict‑of‑interest management; and (iv) disciplined information governance. The manuscript adds a compliance checklist that links each guardrail to statutory or comparative authority, a standard co‑location term sheet, a patient‑facing attribution map, a role‑based data‑access matrix, and a short compliance vignette. The conclusion is practical: approve layering only where legal, physical, and operational separations are demonstrable ex ante; otherwise, refuse licensing to avoid risk transfer to patients and regulatory opacity. [1] Centers for Medicare & Medicaid Services (CMS) [2] Healthcare Services Act (HCSA) by the Ministry of Health Singapore [3] Care Quality Commission (CQC)